Abdominal pain due to cough-induced internal oblique and transverse abdominis hematoma in a patient with H1N1 influenza (Indian Journal of Case Reports, 2019)
Musculoskeletal complications have been observed following severe sustained coughing. Abdominal muscle hematoma can occur as a result of acute or chronic collection of blood following disruption of blood vessels or muscle tear. The condition is uncommon and can mimic other causes of acute abdomen. We report the case of a 60 year old female who presented with severe abdominal pain following 2 days of severe sustained cough. Her abdominal imaging revealed hematoma in the right abdominal wall involving internal oblique and transverse abdominis muscles. She was managed without any surgical intervention, and improved.